Fail-Safe Joints between Copper Alloy (C18150) and Nickel-Based Superalloy (GH4169) Made by Transient Liquid Phase (TLP) Bonding and Using Boron-Nickel (BNi-2) Interlayer - Chengcong Zhang; Amir Shirzadi (Metals, 2021)
Joining heat conducting alloys, such as copper and its alloys, to heat resistant nickel-based superalloys has vast applications in nuclear power plants (including future fusion reactors) and liquid propellant launch vehicles. On the other hand, fusion welding of most dissimilar alloys tends to be unsuccessful due to incompatibilities in their physical properties and melting points. Therefore, solid-state processes, such as diffusion bonding, explosive welding, and friction welding, are considered and commercially used to join various families of dissimilar materials. However, the solid-state diffusion bonding of copper alloys normally results in a substantial deformation of the alloy under the applied bonding load. Therefore, transient liquid phase (TLP) bonding, which requires minimal bonding pressure, was considered to join copper alloy (C18150) to a nickel-based superalloy (GH4169) in this work. BNi-2 foil was used as an interlayer, and the optimum bonding time (keeping the bonding temperature constant as 1030 °C) was determined based on microstructural examinations by optical microscopy (OM), scanning electron microscopy (SEM), energy dispersive spectrometry (EDS), tensile testing, and nano-hardness measurements. TLP bonding at 1030 °C for 90 min resulted in isothermal solidification, hence obtained joints free from eutectic phases. All of the tensile-tested samples failed within the copper alloy and away from their joints. The hardness distribution across the bond zone was also studied.